Divergent Total Synthesis of Indoxamycins A, C, and F1. Issue 50 (31st October 2013) - He, Chi; Zhu, Chenlong; Dai, Zhifeng; Tseng, Chih‐Chung; Ding, Hanfeng
<x xml:space="preserve">Abstract</x> The concise and divergent total synthesis of (−)‐indoxamycins A, C, and F has been completed for the first time by using a tricyclic enone as the common late‐stage intermediate. The key steps of the strategy are based on an Ireland–Claisen rearrangement, a stereodivergent reductive 1, 6‐enyne cyclization, and a tandem 1, 2‐addition/oxa‐Michael/methylenation reaction.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>